An overview of bats microbiota and its implication in transmissible diseases - Federici, Luca; Masulli, Michele; De Laurenzi, Vincenzo; Allocati, Nerino (Frontiers in Microbiology, 2022)
Recent pandemic events have raised the attention of the public on the interactions between human and environment, with particular regard to the more and more feasible transmission to humans of micro-organisms hosted by wild-type species, due to the increasing interspecies contacts originating from human’s activities. Bats, due to their being flying mammals and their increasing promiscuity with humans, have been recognized as hosts frequently capable of transmitting disease-causing microorganisms. Therefore, it is of considerable interest and importance to have a picture as clear as possible of the microorganisms that are hosted by bats. Here we focus on our current knowledge on bats microbiota. We review the most recent literature on this subject, also in view of the bat’s body compartments, their dietary preferences and their habitat. Several pathogenic bacteria, including many carrying multidrug resistance, are indeed common guests of these small mammals, underlining the importance of preserving their habitat, not only to protect them from anthropogenic activities, but also to minimize the spreading of infectious diseases.